Highly Tunable Near‐Room Temperature Ferromagnetism in Cr‐Doped Layered Td‐WTe2. (18th January 2021) - Yang, Li; Wu, Hao; Zhang, Liang; Zhang, Wenfeng; Li, Luying; Kawakami, Tappei; Sugawara, Katsuaki; Sato, Takafumi; Zhang, Gaojie; Gao, Pengfei; Muhammad, Younis; Wen, Xiaokun; et al.
Abstract: The discovery of type‐II Weyl semimetal states in layered transition metal dichalcogenides Td‐WTe2 indicates great potential for novel electronic, spintronic, and quantum devices. Theoretically, the interaction between the topological states and the magnetic ordered states of Td‐WTe2 enables the modulation of Weyl semimetal states by an external magnetic field. However, currently, ferromagnetism in layered Td‐WTe2 is still elusive and rarely observed. In this research, ferromagnetic order into WTe2 using magnetic chromium (Cr) doping with a two‐step Te flux strategy is introduced. The Curie temperature ( T c ) and the ferromagnetic moment are well tuned with a Cr doping concentration. The T c of the Cr‐doped layered Td‐WTe2 could be regulated from 182 to 283 K, which is close to room temperature. The saturation magnetic moment could be changed from 2.26 to 4.20 emu g –1, which is stronger than most values reported for these materials. Most intriguingly, the Cr‐doped layered Td‐WTe2 single crystals still exhibit semimetallic behavior and they possess very large magnetoresistance with obvious Shubnikov de Haas (SdH) quantum oscillations and an anomalous Hall effect. The findings offer feasible ways to induce and tune ferromagnetic orders in layered Td‐WTe2 and thus to control its topological phase with external magnetic fields. Abstract : Near‐room temperature ferromagnetism is achieved by introducing magnetic Cr in layered Td‐WTe2 . The Curie temperature and saturation magnetic moment can be tuned from 182 to 283 K and from 2.26 to 4.20 emu g –1, respectively. Observations of the Shubnikov de Haas oscillation, giant magnetoresistance and topological surface states reveal the first combination of ferromagnetism and topological Weyl semimetal in WTe2 .